ANTHROPOGENIC IMPACT ON THE ATMOSPHERE - Shermatova Zamira Sherzod kizi (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2023)
The air envelope of the Earth, consisting of a mixture of various gases, water vapor and dust, is called the atmosphere. Atmospheric air is the source of respiration for living organisms. It is known that without air a person cannot survive even 5 minutes, while without food he can live about 5 weeks, and without water - about 5 days.